KEMAMPUAN PENERAPAN PEMECAHAN MASALAH PADA MAHASISWA AKUNTANSI - Putri Aliffia; I Gusti Ketut Agung Ulupui (Yayasan Education and Social Center, 2023)
This study aims to determine whether there is an influence between Emotional Intelligence and Creativity on Problem Solving in Accounting in students of the Accounting Study Program State University of Jakarta. Using quantitative methods with a survey approach. The population taken is all active students of the S1 Accounting and S1 Accounting Education study programs class 2018-2020 at the State University of Jakarta. The sampling technique uses probability random sampling to acquire a sample of 186. The instruments used are test instruments and questionnaires. The analysis technique used is multiple analysis. From the results of data testing that has been carried out, it is found that there is a positive and significant influence between Emotional Intelligence on Problem Solving. Then it was found that there was a positive and significant influence between Creativity on Problem Solving. Furthermore, finally, it was found that there was a positive and significant influence between Emotional Intelligence and Creativity on Problem Solving. This study explains that Emotional Intelligence and Creativity can be the determining factors in problem-solving in various cases